2014
DOI: 10.3109/14756366.2014.959512
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium tuberculosisenoyl-acyl carrier protein reductase inhibitors as potential antituberculotics: development in the past decade

Abstract: Mycobacterial enoyl-ACP-reductase, an enzyme contributing in mycolic acids biosynthesis, has been established as promising target of novel antimycobacterial drugs. The development of inhibitors active without previous activation by catalase/peroxidase system (e.g. isoniazid), seems to be rational approach. Catalase/peroxidase system is frequently responsible for resistance. We hereby present a review of direct mycobacterial enoyl-acyl carrier protein reductase inhibitors development in past decade. A special a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 44 publications
(58 reference statements)
0
19
0
Order By: Relevance
“…And finally, we zeroed upon the piperidine moiety. Isoniazid (INH) ( 1.1 ) is a well‐known antitubercular drug with pyridine scaffold and besides this, many six‐membered nitrogen heterocycles have been reported as a promising lead against Mycobacterium tuberculosis , especially as EACP reductase inhibitor . It has been found that 1,4‐di‐substituted piperidine derivative compound 1.2 (Figure ) has more potent antitubercular activity than the 1‐substituted piperidine derivative compound 1.3 (Figure ).…”
Section: Introductionmentioning
confidence: 99%
“…And finally, we zeroed upon the piperidine moiety. Isoniazid (INH) ( 1.1 ) is a well‐known antitubercular drug with pyridine scaffold and besides this, many six‐membered nitrogen heterocycles have been reported as a promising lead against Mycobacterium tuberculosis , especially as EACP reductase inhibitor . It has been found that 1,4‐di‐substituted piperidine derivative compound 1.2 (Figure ) has more potent antitubercular activity than the 1‐substituted piperidine derivative compound 1.3 (Figure ).…”
Section: Introductionmentioning
confidence: 99%
“…Mycobacterium tuberculosis enoyl acyl carrier protein reductase ( Mt InhA) is one of the most attractive enzymes to design and develop novel drugs for tuberculosis therapy and might be a promising target for novel inhibitors active against MDR and XDR MTB . Several benzoxazoles have been studied in respect to the Mt InhA inhibition .…”
Section: Potential Targets Of Benzoxazole‐based Compoundsmentioning
confidence: 99%
“…InhA is the target of isoniazid (INH) and structural analogues such as ethionamide (ETH) activated by the catalase-peroxidase KatG ( Dessen et al., 1995 ). Novel InhA inhibitors (indicated in Table 1 ), unlike INH and ETH, do not require prior activation and have potential for treatment of DR-TB while some are also bactericidal against non-replicating Mtb ( Holas et al., 2015 ; Martínez-Hoyos et al., 2016 ; Flint et al., 2020 ). KasA and KasB are targets of cerulenin, plastensimycin, thiolactomycin, and indazole sulfonamides ( Abrahams et al., 2016 ; Abrahams and Besra, 2018 ).…”
Section: Introductionmentioning
confidence: 99%